Factors affecting physiological parameters of crossbred calves fed on molasses (Indian Journal of Animal Production and Management, 2024)
Thirty two crossbred calves (16 each from Holstein Friesian and Jersey crossbred) at one week of age,  with equal number of male and female were divided into four groups such as Group-1 (fed no molasses),  Group-2 (20gm/ kg calf starter), Group-3 (40gm/ kg calf starter) and Group-4 (60gm/ kg calf starter). Calf  starter (CP- 21% and TDN-75%) composed of crushed maize, wheat bran, rice polish, ground nut cake,  mustard oil cake, skimmed milk powder, mineral mixture and common salts @ 44, 12, 10, 25, 5, 1, 2 and  1 percent respectively. Antibiotic powder Lixen (Cephalexin oral powder) was mixed with calf starter @  20gm/ 100 kg of feed. Recording of physiological parameters such as rectal temperature (RT), pulse rate  (PR) and respiration rate (RR) was done early morning at 8:30 am at fortnight interval from 7th to 97th day  of age. Overall average RR, PR and RT did not differ statistically with respect to breeds and treatment.  However, there was significant (p < 0.01) difference of overall RT due to sex and age. The overall average  RT of female calves was significantly higher (102.26 ± 0.06 0F) than the male calves (101.85 ± 0.06 0F). In  respect of age it was significantly lower on 97th day old calves (101.81 ± 0.14 0F). The overall average PR  differed significantly (p
Keywords: Crossbred calves; Pulse and respiration rate; Rectal temperature